Ultrasonographic findings in hereditary neuropathy with liability to pressure palsies. (February 2015) - Bayrak, Ayse O.; Bayrak, Ilkay Koray; Battaloglu, Esra; Ozes, Burcak; Yildiz, Onur; Onar, Musa Kazim
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: The aims of this study were to evaluate the sonographic findings of patients with hereditary neuropathy with liability to pressure palsies (HNPP) and to examine the correlation between sonographic and electrophysiological findings. Methods: Nine patients whose electrophysiological findings indicated HNPP and whose diagnosis was confirmed by genetic analysis were enrolled in the study. The median, ulnar, peroneal, and tibial nerves were evaluated by ultrasonography. Results: We ultrasonographically evaluated 18 median, ulnar, peroneal, and tibial nerves. Nerve enlargement was identified in the median, ulnar, and peroneal nerves at the typical sites of compression. None of the patients had nerve enlargement at a site of noncompression. None of the tibial nerves had increased cross-sectional area (CSA) values. There were no significant differences in median, ulnar, and peroneal nerve distal motor latencies (DMLs) between the patients with an increased CSA and those with a normal CSA. In most cases, there was no correlation between electrophysiological abnormalities and clinical or sonographic findings. Discussion: Although multiple nerve enlargements at typical entrapment sites on sonographic evaluation can suggest HNPP, ultrasonography cannot be used as a diagnostic tool for HNPP. Ultrasonography may contribute to the differential diagnosis of HNPP and other demyelinating polyneuropathies or compression neuropathies; however, further studies are required.